Analisa Polimorfisme Gen BMP-15 (Bone Morphogeninetic Protein) Sapi PO (Bos Indicus) Dan Hubungannya Dengan Keberhasilan Inseminasi Buatan - Erni Usnia Damayanti; Sri Rahayu (University of Brawijaya, 2013)
ABSTRACT BMP-15 gene is a member of the TGF-β are expressed specifically in developing oocytes in the ovary. The aims of this study was to determine the BMP-15 gene polymorphism in PO cattle using PCR-RFLP method and its relationship to success of artificial insemination of PO cattle. Genomic DNA was isolated from blood of 10 PO cattle using salting out method, obtained randomly from Pasuruan. BMP-15 gene was amplified with 5'-GCTCTGGAATCACAAGGGG-3' as forward primer and 5'-AGAGATGGGGAGCGATGAT-3' as reverse primer. The results of amplification is fragments DNA with the length 350 bp. The amplicon of BMP-15 gene was cut by restriction enzyme HaeIII and polymorphism are indicated by the presence of two haplotypes. The first haplotyp with 2 fragments consist of 100 bp and 200 bp and the second haplotyp with 5 fragments consist of , 100 bp, 125 bp, 200 bp, 300 bp, and 400 bp. In conclusion, there is polymorphism of PO cattle (Bos indicus) BMP-15 gene, however there is no correlation between BMP-15 gene polymorphism with success of artificial insemination of PO cattle.. Keywords : BMP-15 gene, polymorphism, PO cattle.